A conserved sequence motif bridges two protein kinases for enhanced phosphorylation and nuclear function of a splicing factor. (23rd May 2020) - Aubol, Brandon E.; Fattet, Laurent; Adams, Joseph A.
Abstract : The assembly and activation of the spliceosome rely upon the phosphorylation of an essential family of splicing factors known as the serine–arginine (SR) proteins. Although it has been demonstrated recently that two enzyme families, the SR protein kinases (SRPKs) and the Cdc2‐like kinases (CLKs), can function as a complex to efficiently phosphorylate these SR proteins in the nucleus, the molecular features involved in such a connection are unknown. In this study, we identified a group of conserved residues in the large lobe of SRPK1 that interact with the N terminus of CLK1 stabilizing the SRPK1‐CLK1 complex. Mutations in this motif not only disrupt formation of the kinase–kinase complex but also impair SRPK1‐dependent release of the phospho‐SR protein from CLK1. The binding motif potently up‐regulates CLK1‐specific phosphorylation sites, enhances SR protein diffusion from nuclear speckles, and impacts the alternative splicing of several target genes. These results indicate that CLK1 binds a conserved, electronegative surface on SRPK1, thereby controlling SR protein phosphorylation levels for enhanced subnuclear trafficking and alternative splicing regulation. Abstract : Splicing of mRNA is dependent on phosphorylation of an essential family of splicing factors known as SR proteins. Although protein kinases SRPK1 and CLK1 control such phosphorylation in separate cellular compartments, recent studies indicate that they can also function as a kinase–kinase complex in the nucleus. In this study, we report the discovery of a conserved docking region on SRPK1 that binds the N terminus of CLK1, supporting SR protein phosphorylation and subnuclear dynamics.